2021
DOI: 10.1136/bmjopen-2020-044379
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional online survey to determine the prevalence, knowledge, attitude and practice of tobacco cessation among governmental healthcare workers in Qatar

Abstract: ObjectivesOne effective approach of tobacco control is to encourage the role and the participation of healthcare workers in the prevention efforts against tobacco use. This study aimed to determine the prevalence of tobacco use among governmental healthcare workers in Qatar, to assess healthcare workers’ knowledge, attitude and practice of tobacco cessation and to predict factors associated with above average tobacco cessation practice scores.DesignA cross-sectional survey study was conducted among healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
2
10
1
Order By: Relevance
“…This was consistent across other studies among doctors despite disparate tools and knowledge components being assessed [ 11 , 14 , 18 , 19 ]. Also, consistent with other studies, our result demonstrated that primary care doctors with poor knowledge were significantly associated with poor practice [ 10 , 14 – 16 ]. This discrepancy needs to be explored further to explain the poor knowledge scores despite the majority of our primary care doctors having attended training courses for smoking cessation management.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was consistent across other studies among doctors despite disparate tools and knowledge components being assessed [ 11 , 14 , 18 , 19 ]. Also, consistent with other studies, our result demonstrated that primary care doctors with poor knowledge were significantly associated with poor practice [ 10 , 14 – 16 ]. This discrepancy needs to be explored further to explain the poor knowledge scores despite the majority of our primary care doctors having attended training courses for smoking cessation management.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of primary care doctors (73.8% to 93.3%) in Saudi Arabia had shown a good attitude in smoking cessation assessment and management [ 11 , 13 ]. Similarly, healthcare providers in China, Egypt, Africa, and Saudi Arabia had shown a good attitude in smoking cessation assessment and management [ 10 , 16 , 20 – 23 ]. Our result showed near 60% of the primary care doctors reported having a poor attitude.…”
Section: Discussionmentioning
confidence: 99%
“…One of the alternative ways to prevent and reduce smoking prevalence among the community is to empower health professionals by training them to identify waterpipe smokers, educate them about potential harmful effects, and refer them to cessation services. Fortunately, according to a recent study conducted among governmental healthcare workers in Qatar, about 60% of them routinely promoted tobacco cessation interventions, thus being effective in helping users to quit 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in waterpipe smoking has prompted the World Health Organization (WHO) to declare its use as a growing public health concern in its 2015 advisory note 27 . Within the WHO Convention on Tobacco Control (FCTC) framework, Qatar has adopted effective measures for tobacco control such as tax increase, smoke-free policies, ban on advertising and provision of tobacco intervention services along with free-of-cost complete cessation treatment 28 , 29 . Additionally, telephone-based smoking cessation counseling support during the COVID-19 pandemic has also been provided 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Smoking cessation services providing counseling and pharmacological interventions are proven to be cost-effective and improve success rates compared to unaided quit attempts ( Aveyard et al, 2012 , Zwar et al, 2014 ). Fortunately, a recent study among healthcare workers in Qatar showed that almost 60% of them provided tobacco cessation interventions to patients ( AlMulla et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%